Price-dependent profit sharing as an escape from the Bertrand paradox - Øystein Foros; Kåre P. Hagen; Hans Jarle Kind (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this paper we show how an upstream firm can prevent destructive competition among downstream firms producing relatively close substitutes by implementing a price-dependent profit-sharing rule. The rule also ensures that the downstream firms undertake investments which benefit the industry in aggregate. The model is consistent with observations from the market for content commodities distributed by mobile networks.
Keywords: L13; L22; 330; profit-sharing; vertical restraints; investments; competition; Duopol; Unvollkommener Wettbewerb; Spieltheorie; Telekommunikation; Norwegen